2016
DOI: 10.20944/preprints201611.0050.v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Car Tourism in China: The Mediation Effect of Perceived Value and Tourist Satisfaction on the Relationship between Destination Image and Loyalty

Abstract: This study aims to test a model linking destination image, perceived value, tourist satisfaction, and tourist loyalty. Based on a sample of 300 tourists travelling by car from the World Natural Heritage Site of Tianchi, China, a new model of destination image was explored and data were analysed using partial least squares structural equation modelling (PLS-SEM). The results show that perceived value and satisfaction are direct antecedents of destination loyalty. Above all, perceived value and tourist satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 39 publications
0
2
0
4
Order By: Relevance
“…Taheri et al (2014) emphasized the need for further research on the concept of tourist engagement, highlighting that it encompasses qualities such as attachment, emotional connection, commitment, and devotion [38]. Wang et al (2015) applied the theory of customer engagement to the tourism industry and suggested that due to the unique nature of cultural heritage tourist destinations, tourists have a greater demand for engagement [39]. Tourist engagement include the person's cognitive, emotional, and behavioral connections with the destination, which are established through communication, interaction, or other non-transactional behaviors, all of which are based on tourism expectations.…”
Section: Intermediary Role Of Tourist Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…Taheri et al (2014) emphasized the need for further research on the concept of tourist engagement, highlighting that it encompasses qualities such as attachment, emotional connection, commitment, and devotion [38]. Wang et al (2015) applied the theory of customer engagement to the tourism industry and suggested that due to the unique nature of cultural heritage tourist destinations, tourists have a greater demand for engagement [39]. Tourist engagement include the person's cognitive, emotional, and behavioral connections with the destination, which are established through communication, interaction, or other non-transactional behaviors, all of which are based on tourism expectations.…”
Section: Intermediary Role Of Tourist Engagementmentioning
confidence: 99%
“…The questionnaire consists of four modules: object-related authenticity, existence authenticity, tourist loyalty, and demographic variables. The measurement of object authenticity and existence authenticity is based on the methods proposed by Kolar 2015) [39] and includes five dimensions: identification (IF), attention (AT), enthusiasm (ES), interaction (IA), and integration (IG). Tourist loyalty is measured using the methods proposed by Bai et al ( 2010) [44] and Day et al (1969) [45], with three questions.…”
Section: Variable Measurementmentioning
confidence: 99%
“…Menurut Kotler dan Keller (2018) nilai persepsi pelanggan merupakan perbedaan antara perspektif evaluasi pelanggan dari semua manfaat dan semua biaya penawaran dan alternatif yang dirasakan. Menurut Wang et al (2016) Perceived value digambarkan sebagai penilaian keseluruhan yang dibuat wisatawan berdasarkan perbandingan utilitas atau manfaat mereka dan biaya atau pengorbanan yang dirasakan terkait dengan destinasi. Menurut Choi et al (2017) Praktisi dan cendekiawan mendapatkan nilai yang dirasakan.…”
Section: Tinjauan Literatur Perceived Valueunclassified
“…Menurut Cibro dan Hudrasyah (2017) kepuasan pelanggan didefinisikan sebagai ringkasan tanggapan yang dibuat berdasarkan pengalaman pelanggan saat mencoba suatu produk atau layanan. Menurut Wang et al (2016) Kepuasan, yang didefinisikan sebagai evaluasi komprehensif produk dan layanan destinasi, adalah salah satu konsep terpenting daya saing pemasaran modern. Kepuasan pariwisata telah dipelajari secara ekstensif di sektor pariwisata.…”
Section: Satisfactionunclassified
See 1 more Smart Citation